Efeitos de macrófitas flutuantes nos processos evaporativos em mesocosmos - Machado, Ugo Leonardo Rodrigues (2023)
The semi-arid region of Brazil, characterized by water scarcity, demands sustainable water resource management. With low relative precipitation and high evaporation rates, reservoirs play a vital role in water supply and irrigation. The limited water availability, due to water deficit and pollution in Ceará, is a central issue: in many reservoirs, water is in eutrophic (or hyper-eutrophic) state, with the massive presence of macrophytes. Evaluating the environmental impact of macrophytes in mesoscale reservoirs is necessary to understand their role in the water balance. The approach used was to compare evapotranspiration in areas with macrophytes and evaporation in unvegetated areas. The scientific question is whether macrophytes alter the evaporative pattern in reservoirs on the mesocosm scale. The hypothesis is that the floating macrophyte Eichhornia crassipes increases evaporative losses in the reservoir. The objective is to compare evapotranspiration with floating macrophytes in mesocosm tanks and clear-water evaporation under the same condition. Measurements also include the water trophic state index, Class A pan evaporation, and Penman-equation evaporation assessment. The similarity test confirmed statistical equivalence between the two experimental mesocosm tanks with a 5% significance level, allowing for only two treatments: Tank without macrophytes (TS) and Tank with macrophytes (TC). Conducted at the UFC Pici Campus in Fortaleza, Ceará, from June to December 2022, the experiment water consistently exhibited a hyper-eutrophic state in both tanks. The average evaporation in Treatment TS was 6.78 mm.day⁻¹, while the average evapotranspiration in TC was 8.75 mm.day⁻¹. The average evaporation rates in the Class A pan were 7.51 mm.day⁻¹, and according to the Penman Equation, evaporative losses were 7.50 mm.day⁻¹. Considering two mesoscale tanks in a sub-humid tropical environment with hyper-eutrophic water, we conclude that evapotranspiration in a reservoir with macrophytes (Eichhornia crassipes) exceeds evaporation in the same reservoir without macrophytes by 20% to 29%. We also observe that evaporation in the mesoscale tank (19.6 m²) with hyper-eutrophic water is 10% lower than that in the Class A pan (1.14 m²) with oligotrophic water. Class A pan evaporation is similar to that calculated by the Penman method. With this research, we hope to contribute to a better understanding of the impact of macrophytes on reservoir evaporation in the Brazilian Semi-Arid region.